Using red blood cell distribution width to predict death after abdominal aortic aneurysm rupture - Wanghai Li; Tao Liao; Yan Zhang; Chengzhi Li (BMC Cardiovascular Disorders, 2023)
Abstract Background An abdominal aortic aneurysm is a life-threatening enlargement in the major vessel at the abdomen level. This study investigated the associations between different levels of red blood cell distribution width and all-cause mortality among patients with abdominal aortic aneurysm rupture. It developed predictive models for all-cause mortality risk. Methods This was a retrospective cohort study using 2001 to 2012 MIMIC-III dataset. The study sample included 392 U.S. adults with abdominal aortic aneurysms who were admitted to ICU after the aneurysm rupture. Then we used two single-factor and four multivariable logistic regression models to examine the associations between different levels of red blood cell distribution and all-cause mortality (30 days and 90 days), controlling for demographics, comorbidities, vital signs, and other laboratory measurements. The receiver operator characteristic curves were calculated, and the areas under the curves were recorded. Results There were 140 (35.7%) patients with an abdominal aortic aneurysm in the red blood cell distribution width range between 11.7 and 13.8%, 117 (29.8%) patients in the range between 13.9 and 14.9%, and 135 (34.5%) patients in the range between 15.0 and 21.6%. Patients with higher red blood cell distribution width level (> 13.8%) tended to have a higher mortality rate (both 30 days and 90 days), congestive heart failure, renal failure, coagulation disorders, lower hemoglobin, hematocrit, MCV, red blood cell count, higher levels of chloride, creatinine, sodium, and BUN (All P < 0.05). Results of multivariate logistic regression models indicated that patients with higher red blood cell distribution width levels (> 13.8%) had the highest statistically significant odd ratios of 30 days and 90 days of all-cause mortality than lower red blood cell distribution width levels. The area under the RDW curve was lower (P = 0.0009) than that of SAPSII scores. Conclusions Our study found that patients with abdominal aortic aneurysm rupture with a higher blood cell distribution had the highest risk of all-cause mortality. Using the blood cell distribution width level in patients with abdominal aortic aneurysm rupture to predict mortality should be considered in future clinical practice.